Kalimat Imperatif dalam Iklan Layanan Masyarakat Berbahasa Arab Terkait Covid-19 di SBS Australia - Trian Ramadhan Nuryadin; Wagiati (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2020)
Social networking media became the main media to spread public service announcements related to Covid-19 during a pandemic to prevent the spread of this outbreak. This study focuses on imperative sentences on public service Arabic announcements related to Covid-19 issued by SBS Australia. The purpose of this study is to describe the structure of imperative sentence forms in these advertisements syntactically and to group them into imperative sentence types according to Alwi (2010). This research is included in the research type of descriptive analysis research. The data analysis method used in this study is a method of distribution with the basic technique for direct elements (BUL) which is used to describe and analyze data from data sources. This study found as many as; 5 data are categorized as imperative commands or ordinary orders, 1 data are categorized as imperative subtle commands, 2 data are categorized as imperatives and invitations, 2 data are categorized as imperative prohibitions or negative commands. In addition, the imperative sentence in this ad is preceded by the structure of the predicate-object-complement-description sentence.